USING THE EARNINGS MANAGEMENT TO REDUCTION OF POLITICAL COSTS: AN ANALYSIS FROM DVA - Dallabona, Lara Fabiana; Martins, José Augusto Sousa; Klann, Roberto Carlos (Contextus - Revista Contemporânea de Economia e Gestão, 2014)
The study aims to identify the relationship among the distribution of added value to the government and the size of firms with earnings management practices. We conducted descriptive, documental and quantitative research, with application of multiple linear regression on a sample of 135 companies. The results show that the largest portion of the amount distributed was for the government through taxes and contributions, thus suggesting that the analyzed companies incur political costs due to high taxes in their operations. It was found that earnings management is negatively related to political costs and positively related to the size of companies, although not with statistical significance. We conclude, therefore, that the practice of earnings management cannot be explained by the distribution of value to government and company size.